The role of ovariectomy in the formation of endogenous intoxication syndrome in the late period of aftersceletal and combined craneoskeletal injury in experiment - Mashevskyi, A. S.; Hudyma, A. A. (Journal of Education, Health and Sport, 2016)
Mashevskyi A. S., Hudyma A. A. The role of ovariectomy in the formation of endogenous intoxication syndrome in the late period of aftersceletal and combined craneoskeletal injury in experiment Journal of Education, Health and Sport. 2016;6(10):423-429. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.164170 http://ojs.ukw.edu.pl/index.php/johs/article/view/3968 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016. УДК 618.177-06:616-008.6-02:616.711/714-001-036.7]-092.9 THE ROLE OF OVARIECTOMY IN THE FORMATION OF ENDOGENOUS INTOXICATION SYNDROME IN THE LATE PERIOD OF AFTERSCELETAL AND COMBINED CRANEOSKELETAL INJURY IN EXPERIMENT A. S. Mashevskyi, A. A. Hudyma SHEE “Ternopil State Medical University named after I.Ya. Horbachevskyi, Ministry of Health of Ukraine” Summary Causing combined traumatic brain injury in conditions of gonads removal is accompanied by increasing level of endogenous intoxication, manifested by the accumulation of fractions MSM254 and MSM280 in blood within two months of post-traumatic period and is significantly higher than in animals with skeletal trauma and injured animals without ovariectomy. This result demonstrates the important role of estrogens in the formation of endogenous intoxication syndrome in the conditions of mechanical injury. Keywords: ovariectomy, craneoskeletal injury, endogenous intoxication.